Penggunaan Tepung Buah Nipah (Nyfa Fruticans Wurmb) sebagai Ekstender pada Perekat Urea Formaldehid untuk Papan Partikel - Noor Mirad Sari; Rosidah Rosidah; Muhamad Yuliadi Rahman (Jurnal Ilmu Kehutanan, 2008)
Utilization of Nypa Fruit Flour (Nyfa Fruticans Wurmb) as an Extender in Urea Formaldehyde Adhesive for Particle BoardNipah fruit (Nyfa Fruticans Wurmb) is a seasonal forest product abundantly produced in each season. Nipah fruit flour is believed to also function as an extender during adhesion process of wood products such as plywoods and particle boards. The study aims to determine the right composition between nipah fruit flour and industrial flour as an extender which, together with urea formaldehyde adhesive, to be applied to particle board. Results revealed that the composition of 50% industrial flour and 50% nipah fruit flour (A3 treatment) gave the highest Modulus of Elasticity (MoE) with value of 16,833.90 kg/cm2 while average value of all treatment was 12,131.41 kg/cm2. The MoE of A3 treatment fulfilled the national standard (SNI) of 15.000 kg/cm2. As for MoE, the composition of A3 (50% industrial flour and 50% nipah fruit flour) was the most efficient mixture in producing the highest MoR with 119.30 kg/cm2. The MoR value for A3 also fulfilled the national standard of 80 kg/cm2. Comparing between treatments, all other treatment gave the MoE value less than reuired by national standard. The particle boards produced by other treatments were easily bent due to high carbohydrate and water content that weaken the elasticity of boards. For MoR character, all treatments gave value as required by national standard (higher than 80 kg/cm2) except treatment A5 which gave the value of less than required (76,36 kg/cm2).